Analisis Bibliometrik Vos Viewer tentang Centre of Excellence Lembaga Diklat - Irfan Abraham (STKIP PGRI SITUBONDO, 2022)
This article was written with the aim of providing a deep and comprehensive understanding to the parties, especially decision makers in the world of education related to the Center of Excellence, an educational and training institution. What and how the Center of Excellence will be written in this study. This type of research uses descriptive qualitative. This research method is through literature study with a bibliometric approach. The object of research is the bibliographical manuscript data obtained from Scopus, Google Scholar and then mapped and analyzed using Vos Viewer software. Vos Viewer bibliometric analysis results display network visualization, overlay visualization and density visualization. Based on the results of the research study, it shows that there are 3 indicators that make an institution a Center of Excellence, namely, policy alignment, professional teaching staff, and recognition from other institutions.